Production and Monitoring of Neutron Flux by Activation Detectors - Haysak Ivan; Martishichkin Vasyl; Harapko Yevgen; Holomb Robert; Katovsky Karel (EPJ Web of Conferences, 2021)
The neutron generation technique was tested on the microtron M-10 with an output electron beam of 8.7 MeV. Given the low energy that the microtron can provide to electrons, the bremsstrahlung induced photonuclear reaction 9Be (γ, n), which has a low threshold, was chosen for neutron generation. Cobalt and indium targets were tested as activation detectors to estimate the neutron flux density. In the cobalt target, the isomeric state of 60mCo with an energy of 58.6 keV and a half-life of 10.5 minutes is well activated. Two well-known additional gamma lines of standard cobalt source permit to clarify the absolute value of the neutron flux. The activated indium target has four gamma lines bound to the 116mIn isomer β- decaying with the half-life of 54.4 minutes, what is convenient for measurement of gamma spectrum. Despite the low energy of the output electron beam, at a beam intensity of 5 μA it is possible to obtain an almost isotropic neutron flux of 107 n/(s∙cm2).